Assessment and Monitoring of Moisture Content Variation in Compacted Tropical Soil Using GPR Data - Pizarro Marchena, Irving; Françosob, M.T.; Moraes Treiber, H.; de Oliveira Stenico, N. (Revista Ingeniería de Construcción, 2023)
The rapid deterioration and unsatisfactory performance of highway pavements are also related to the variation and excessive accumulation of moisture in the subgrade and in constituent layers. Hence, moisture control is essential to ensure, in part, the durability and good performance of these types of structures. Ground Penetration Radar (GPR) has proven to be a useful potential alternative for this purpose, given its non-invasive characteristics, preserving the integrity of the site under observation, in addition to the ability to quickly and continuously collecting data. This study aims at evaluating the sensitivity of the GPR to moisture changes and to investigate the influence that calibration models have on predicting moisture content in a compacted tropical soil. Deformed lateritic soil samples were used and subjected to physical properties' characterization and compaction tests. A 1600 MHz antenna GPR was used for data acquisition in a controlled laboratory environment. On the whole, the results showed that GPR is a promising alternative, with both satisfactory accuracy in moisture assessment and sensitivity when monitoring changes in moisture content in compacted soils.